Attitudinal Assessment of Youth Technopreneurial Engagement in Olukayode Market, Akure Metropolis - Oke, Jonathan; Ahmodu, Abdul-Lateef Olamide (Acta Universitatis Danubius. Œconomica, 2022)
The study examines the attitudinal assessment of youth technopreneurial engagement in the olukayode market, Akure metropolis. The study adopted a survey research design with a population of (243) registered technopreneurial Micro, Small and Medium Enterprises (MSMEs) in Ondo State Ministry of Commerce and Industry. The sample size of the study was (152) using the Krejcie and Morgan sample technique to select the sample size. A primary source of data was used to elicit the data through the administration of a questionnaire. Crambach's alpha coefficient value of 0.808 indicates that the instrument is acceptable. The method of data analysis used was simple percentage, descriptive and factor analysis to test the research questions. The findings revealed that unemployment remain the major factor that motivated the youths to engage in technopreneurship. Also, technopreneurial education enhances youth engagement as well as the socioeconomic status of technopreneurs revealed that there was low family income among the respondents while the technopreneurial services as predicted that majority of women engaged in the sales of computer than other technopreneurial businesses. The study concludes that information communication technology plays a positive significant role in enhancing the youths' technopreneurship engagement skills in Nigeria. Based on these findings, the study, therefore, recommends that the government should be the driving force behind the country's technological entrepreneurship development. Also, the social investment funds should be adequately accessible for the youths, thereby reducing unemployment and increasing the economic growth of the country.